Fatal leptospirosis in southern sea otters from Central California: pathologic findings and detection of Leptospira interrogans - Margaret E. Martinez; Pádraig J. Duignan; Katherine C. Prager; Cara L. Field; Mary E. Gomes; Rinosh Mani; Lilian Carswell; Tim Tinker; Joseph Tomoleoni; Michael Murray; Ri K. Chang; James O. Lloyd-Smith; et al. (Frontiers in Marine Science, 2026)
Leptospira interrogans serovar Pomona infections cause periodic outbreaks in California sea lions (CSLs; Zalophus californianus ) and sporadic deaths in phocids. However, the frequency of infection and associated health impacts remain uncharacterized in sympatric threatened southern sea otters (SSOs; Enhydra lutris nereis ), which serve as important sentinels of coastal health. Given the broad impacts of L. interrogans on other marine mammals, our objective was to screen selected SSOs for infection, determine whether leptospirosis contributes to SSO mortality, and describe leptospiral-associated lesions. A retrospective review (2005–2025) identified 19 candidate cases that underwent detailed review, including Leptospira immunohistochemistry (IHC), serology, and polymerase chain reaction (PCR), with a special focus on renal and hepatic lesions. Kidney samples were PCR-positive for 74% (14/19) of suspected cases. For eight of these, DNA sequence-based serogroup typing detected L. interrogans serogroup Pomona. Seven of the 14 PCR-positive leptospirosis cases were classified as fatal based on positive renal IHC and moderate to severe tubulointerstitial nephritis. All fatal cases had anti- L. interrogans serovar Pomona antibody titers ≥1:25,600. The remaining seven PCR-positive cases were considered nonfatal leptospirosis due to minimal and/or unrelated renal lesions and negative IHC. Nonfatal Leptospira -infected cases ranged from seronegative to low positive (1:400) for serovar Pomona. Antibody titers for Leptospira PCR-negative cases were negative. In fatal cases, gross renal changes were often inapparent or characterized by miliary white cortical foci. Renal histologic lesions included tubulointerstitial nephritis, acute tubular necrosis, and suppurative tubulitis with intratubular bacteria, along with positive IHC staining for leptospiral antigen in the lesions. Gross hepatic changes were also inapparent in fatal cases, and histologic lesions were rare, characterized in one animal by hepatocellular dissociation and in two sea otters by limited leptospiral antigen detection by IHC. Most Leptospira -infected sea otters (71%, 10/14) stranded during higher rainfall months in California, suggesting possible land-to-sea transmission from terrestrial hosts. Given these findings, and because L. interrogans serovar Pomona infections have been confirmed in sympatric CSLs and terrestrial mammals from adjacent watersheds, a focused investigation of potential marine and terrestrial disease transmission dynamics could provide new information to reduce SSO mortalities.

Supporting frontline workers in the biodiversity crisis by empowering and enabling practitioners to embrace conservation evidence - Steven J. Cooke; Kevin A. Adeli; Trina Rytwinski; Andrew N. Kadykalo; Jennifer F. Provencher; Vivian M. Nguyen; Joseph R. Bennett; Christina M. Davy; Rachel T. Buxton; Dalal E. L. Hanna; Nathan Young; Jesse C. Vermaire; et al. (Socio-Ecological Practice Research, 2026)

Commercial scale test of purple sea urchin roe enhancement aquaculture - Xavier J. Smith; Tim Dempster; Michael Salini; David Francis; Fletcher Warren-Myers (Aquaculture, 2026)

The benthic genus Prorocentrum (Dinophyceae) in Aotearoa New Zealand and Rangitāhua Kermadec Islands: Genetic diversity, distribution, and diarrhetic shellfish toxin profile - Tomohiro Nishimura; J. Sam Murray; Kirsty F. Smith; Lucy Thompson; Joshua Fitzgerald; Emillie Passfield; Muharrem Balci; D. Tim Harwood; Sarah Challenger; Masao Adachi; Lesley L. Rhodes (Harmful Algae, 2026)

Global Analysis of Shallow Underwater Fish Observation Research: 70 Years of Progress, Persistent Geographic Biases and a Path Forward - Angus John van Wyk; Rick D. Stuart‐Smith; Jordan S. Goetze; Eva Maire; Elodie Heyns‐Veale; Kaylee Smit; Tim J. Langlois; M. Aaron MacNeil; Alejandro Pérez‐Matus; Amanda T. Lombard; Ana Carolina; Christy Semmens; et al. (Fish and Fisheries, 2026)
Marine ecosystems are increasingly threatened by overfishing, pollution, coastal development and climate change, underscoring the need for long‐term, representative information on key fish populations and habitats to inform management and policy. Underwater fish observation (UFObs) techniques, such as Underwater Visual Census (UVC), stereo‐Baited Remote Underwater Video (stereo‐BRUV) and Remotely Operated Vehicles (ROVs), play a key role in sustaining long‐term data collection. Despite technological advancements, gaps persist in understanding research focus, geographic distribution and methodological biases inherent in these methods. We conducted a scientometric analysis of 1443 peer‐reviewed publications (1953–2023), employing natural language processing and network analysis to map the research landscape. We identified 15 knowledge clusters, including marine protected areas, apex predator conservation and reef ecosystems. Our findings reveal increasing use of BRUVS and ROVs in studies of marine protected areas and subsea infrastructure, while UVC remains prevalent in shallow coral reef research. Geographic representation is skewed, with the field dominated by researchers based in Australia and the United States, and underrepresented in Africa and Southeast Asia. This imbalance highlights the need for more inclusive, globally coordinated monitoring and reporting. Our results underscore the urgency of standardising protocols within each observation method and developing interoperable reporting frameworks across techniques to maximise data comparability and foster international collaboration. Addressing these challenges will strengthen the field's capacity to inform global conservation strategies and support sustainable fisheries management.

Adaptive management and optimisation of stream monitoring network design through an integrated monitoring and modelling approach - Vaughn Grey; Kate Smith-Miles; Belinda E. Hatt; Rhys A. Coleman; Tim D. Fletcher (Journal of Hydrology, 2026)

Assessing patient risk, benefit, and outcomes in drug development: a decade of sorafenib clinical trials - Logan Corwin; Joanna George; Eli Paul; Tim Smith; Griffin K. Hughes; Ryan McIntire; Brooke Gardner; Andriana Peña; Chase Ladd; Kirstien Minley; Kate Riley; Alyson Haslam; et al. (European Journal of Clinical Pharmacology, 2026)

Ingestion of Alexandrium pacificum Cysts by a Deposit Feeder: An Option for Ecosystem‐Based Approach Benefiting Aquaculture and Coastal Communities? - Leonardo N. Zamora; Kirsty F. Smith; Jacqui Stuart; D. Tim Harwood; Shenae L. Wales; Emillie M. F. Passfield; Lincoln Mackenzie (New Zealand Journal of Marine and Freshwater Research, 2026)
Harmful algal blooms caused by the paralytic shellfish toxin‐producing species Alexandrium pacificum have increased in recent years in one of the most important aquaculture regions of New Zealand, the Marlborough Sounds. Reoccurring blooms have created large cysts beds in the sediments throughout the sounds. In this region, large populations of the sea cucumber Australostichopus mollis can also be found. These deposit feeders potentially ingest the resting cysts of A. pacificum when feeding. To investigate this, we used molecular techniques to evaluate and quantify cyst ingestion, and chemical analysis to determine toxin accumulation in A. mollis . Results indicate that sea cucumbers can act as bioindicators of cyst distribution through their selective feeding behaviours, with high concentrations of A. pacificum DNA in foregut samples. Sea cucumbers could also serve as a biocontrol tool, as A. pacificum DNA concentrations decreased along the digestive tract, from the foregut to the hindgut, indicating a reduction in cyst number during the digestion process. Furthermore, no toxin accumulation was detected in the sea cucumber tissue. These encouraging results open the possibility for further research to evaluate the efficiency of integrated biocontrol management and the emergence of a multi‐impact aquaculture sector around this iconic New Zealand echinoderm.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Harnessing the strengths of machine learning and geostatistics to improve streamflow prediction in ungauged basins; the best of both worlds - Vaughn Grey; Tim D. Fletcher; Kate Smith-Miles; Belinda E. Hatt; Rhys A. Coleman (Journal of Hydrology, 2025)

The economic value of improving the ecological condition of the Saskatchewan River Delta, Canada - Elisabeta Lika; Ken Belcher; Tim Jardine; Sabine Liebenehm; Patrick Lloyd-Smith; Graham Strickert (Ecosystem Services, 2025)

High ciguatoxin-producing Gambierdiscus clade (Gonyaulacales, Dinophyceae) as a source of toxins causing ciguatera poisoning - Shauna A. Murray; Arjun Verma; Mona Hoppenrath; D. Tim Harwood; J. Sam Murray; Kirsty F. Smith; Richard Lewis; Sarah C. Finch; Shikder Saiful Islam; Amna Ashfaq; Caroline Dornelles De Azevedo; Christopher J.S. Bolch (Science of The Total Environment, 2025)

The Utility of Fish Population Monitoring and Forecast Trigger Development for Designing Adaptive Aquatic Monitoring Plans for Large Industrial Developments - Carolyn JM Brown; Tim J. Arciszewski; R. Allen Curry; D. Scott Smith; Kelly R. Munkittrick (Environmental Management, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

ApoM-bound S1P acts via endothelial S1PR1 to suppress choroidal neovascularization and vascular leakage - Bongnam Jung; Hitomi Yagi; Andrew Kuo; Tim F. Dorweiler; Masanori Aikawa; Taku Kasai; Sasha A. Singh; Andrew J. Dannenberg; Zhongjie Fu; Colin Niaudet; Lois E. H. Smith; Timothy Hla (Angiogenesis, 2025)

The EGS Collab project: Outcomes and lessons learned from hydraulic fracture stimulations in crystalline rock at 1.25 and 1.5 km depth - Tim Kneafsey; Pat Dobson; Doug Blankenship; Paul Schwering; Mark White; Joseph P. Morris; Lianjie Huang; Tim Johnson; Jeff Burghardt; Earl Mattson; Ghanashyam Neupane; Chris Strickland; et al. (Geothermics, 2025)

Engineering Performance and Spatial Models Highlight Key Considerations for Supporting Broadscale Replacement of Environmentally Sensitive (ES) Vessel Moorings - Lincoln S. Wong; Andrew Martini; Tim P. Lynch; Carlie Devine; Lauren Hardiman; Felicity R. McEnnulty; Rick D. Stuart-Smith; D. Jeff Ross (Coastal Management, 2025)

Structured decision-making shows broad support from diverse stakeholders for habitat conservation and restoration in Kenya’s Central Highlands - Gwili E.M. Gibbon; Martin Dallimer; Hassan Golo; Humphrey Munene; Charlene A. Wandera; Monda N. Edson; Jane C. Gachura; Tim Hobbs; Festus Ihwagi; Stephen R. Ikhamati; Samson K. Ikiara; David Kimathi; et al. (Land Use Policy, 2024)

Revival of cryopreserved larvae from the important aquaculture species Pacific White Shrimp (Litopenaeus vannamei) using vitrification and ultra-rapid laser warming - Kieran T. Smith; Kanav Khosla; Guebum Han; Tim Humphrey; Nicholas Phelps; John Bischof (Cryobiology, 2024)

Correction: Improving the communication of multifactorial cancer risk assessment results for different audiences: a co-design process - Francisca Stutzin Donoso; Tim Carver; Lorenzo Ficorella; Nichola Fennell; Antonis C. Antoniou; Douglas F. Easton; Marc Tischkowitz; Fiona M. Walter; Juliet A. Usher-Smith; Stephanie Archer (Journal of Community Genetics, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Improving the communication of multifactorial cancer risk assessment results for different audiences: a co-design process - Francisca Stutzin Donoso; Tim Carver; Lorenzo Ficorella; Nichola Fennell; Antonis C. Antoniou; Douglas F. Easton; Marc Tischkowitz; Fiona M. Walter; Juliet A. Usher-Smith; Stephanie Archer (Journal of Community Genetics, 2024)
Background Multifactorial cancer risk prediction tools, such as CanRisk, are increasingly being incorporated into routine healthcare. Understanding risk information and communicating risk is challenging and healthcare professionals rely substantially on the outputs of risk prediction tools to communicate results. This work aimed to produce a new CanRisk report so users can directly access key information and communicate risk estimates effectively. Methods Over a 13-month period, we led an 8-step co-design process with patients, the public, and healthcare professionals. Steps comprised 1) think aloud testing of the original CanRisk report; 2) structured feedback on the original report; 3) literature review; 4) development of a new report prototype; 5) first round of structured feedback; 6) updating the new report prototype; 7) second round of structured feedback; and 8) finalising and publishing the new CanRisk report. Results We received 56 sets of feedback from 34 stakeholders. Overall, the original CanRisk report was not suitable for patients and the public. Building on the feedback, the new report has an overview of the information presented: section one summarises key information for individuals; sections two and three present information for healthcare professionals in different settings. New features also include explanatory text, definitions, graphs, keys and tables to support the interpretation of the information. Discussion This co-design experience shows the value of collaboration for the successful communication of complex health information. As a result, the new CanRisk report has the potential to better support shared decision-making processes about cancer risk management across clinical settings.

Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

Benefits of calorie restriction in mice are mediated via energy imbalance, not absolute energy or protein intake - Daniel L. Smith; Sharon E. Mitchell; Maria S. Johnson; Victoria K. Gibbs; Stephanie Dickinson; Beate Henschel; Rui Li; Kathryn A. Kaiser; Daniella E. Chusyd; Andrew W. Brown; David B. Allison; John R. Speakman; et al. (GeroScience, 2024)
Caloric restriction (CR) results in reduced energy and protein intake, raising questions about protein restriction’s contribution to CR longevity benefits. We kept ad libitum ( AL )–fed male C57BL/6J mice at 27°C (AL27) and pair-fed (PF) mice at 22°C (22(PF27)). The 22(PF27) group was fed to match AL27 while restricted for calories due to cold-induced metabolism. The 22(PF27) mice had significantly lower body weight, lean mass, fat mass, leptin, IGF-1, and TNF-α levels than AL27 mice ( p <0.001 for all). Manipulations over ~11 weeks resulted in significant differences in body temperature, physical activity, and expression of key genes linked to hunger in the hypothalamus. Survival was significantly greater in 22(PF27) compared to AL27 overall ( p <0.001). CR in the context of equivalent energy and protein intake resulted in hormonal, metabolic, and physiological benefits and extended longevity. Hence, energy imbalance, rather than low energy or protein intake per se, mediates the benefits of CR.

Analysis of irregularly sampled stream temperature time series: challenges and solutions - Vaughn Grey; Belinda E. Hatt; Tim D. Fletcher; Kate Smith-Miles; Rhys A. Coleman (Journal of Hydrology, 2024)

Population parameters and conservation implications for one of the world's rarest marine fishes, the red handfish ( Thymichthys politus ) - Tyson J. Bessell; Rick D. Stuart‐Smith; Olivia J. Johnson; Neville S. Barrett; Tim P. Lynch; Andrew J. Trotter; Jemina Stuart‐Smith (Journal of Fish Biology, 2024)
Population estimates are required for effective conservation of many rare marine species, but can be difficult to obtain. The critically endangered red handfish ( Thymichthys politus ) is a coastal anglerfish known only from two fragmented populations in southeast Tasmania, Australia. It is at a high risk of extinction due to low numbers, loss of habitat, and the impacts of climate change. To aid conservation efforts, we provide the first empirical population size estimates of red handfish and investigate other important aspects of the species' life history, such as growth, habitat association, and movement. We surveyed both red handfish local populations via underwater visual census on scuba over 3 years and used photographic mark‐recapture techniques to estimate biological parameters. In 2020, the local adult population size was estimated to be 94 (95% confidence interval [CI] 40–231) adults at one site, and 7 (95% CI 5–10) at the other site, suggesting an estimated global population of 101 adults. Movement of individuals was extremely limited at 48.5 m (± 77.7 S.D. ) per year. We also found evidence of declining fish density, a declining proportion of juveniles, and increasing average fish size during the study. These results provide a serious warning that red handfish are likely sliding toward extinction, and highlight the urgent need to expand efforts for ex situ captive breeding to bolster numbers in the wild and maintain captive insurance populations, and to protect vital habitat to safeguard the species' ongoing survival in the wild.

Using the IUCN Environmental Impact Classification for Alien Taxa to inform decision‐making - Sabrina Kumschick; Sandro Bertolino; Tim M. Blackburn; Giuseppe Brundu; Katie E. Costello; Maarten de Groot; Thomas Evans; Belinda Gallardo; Piero Genovesi; Tanushri Govender; Jonathan M. Jeschke; Katharina Lapin; et al. (Conservation Biology, 2024)
The Environmental Impact Classification for Alien Taxa (EICAT) is an important tool for biological invasion policy and management and has been adopted as an International Union for Conservation of Nature (IUCN) standard to measure the severity of environmental impacts caused by organisms living outside their native ranges. EICAT has already been incorporated into some national and local decision‐making procedures, making it a particularly relevant resource for addressing the impact of non‐native species. Recently, some of the underlying conceptual principles of EICAT, particularly those related to the use of the precautionary approach, have been challenged. Although still relatively new, guidelines for the application and interpretation of EICAT will be periodically revisited by the IUCN community, based on scientific evidence, to improve the process. Some of the criticisms recently raised are based on subjectively selected assumptions that cannot be generalized and may harm global efforts to manage biological invasions. EICAT adopts a precautionary principle by considering a species’ impact history elsewhere because some taxa have traits that can make them inherently more harmful. Furthermore, non‐native species are often important drivers of biodiversity loss even in the presence of other pressures. Ignoring the precautionary principle when tackling the impacts of non‐native species has led to devastating consequences for human well‐being, biodiversity, and ecosystems, as well as poor management outcomes, and thus to significant economic costs. EICAT is a relevant tool because it supports prioritization and management of non‐native species and meeting and monitoring progress toward the Kunming–Montreal Global Biodiversity Framework (GBF) Target 6.

Changes in inundation drive carbon dioxide and methane fluxes in a temperate wetland - Erin Hassett; Gil Bohrer; Lauren Kinsman-Costello; Yvette Onyango; Talia Pope; Chelsea Smith; Justine Missik; Erin Eberhard; Jorge Villa; Steven E. McMurray; Tim Morin (Science of The Total Environment, 2024)

The impact of body mass index and physical disability on home-based anal self-sampling - Jenna Nitkowski; Maria E. Fernandez; Tim Ridolfi; Elizabeth Chiao; Anna R. Giuliano; Vanessa Schick; Michael D. Swartz; Jennifer S. Smith; Alan G. Nyitray (Cancer Causes & Control, 2024)

Investigating tritrophic interactions using bioenergetic demographic models - Gioele Passoni; Tim Coulson; Francesca Cagnacci; Peter Hudson; Daniel R. Stahler; Douglas W. Smith; Shelly Lachish (Ecology, 2024)
A central debate in ecology has been the long‐running discussion on the role of apex predators in affecting the abundance and dynamics of their prey. In terrestrial systems, research has primarily relied on correlational approaches, due to the challenge of implementing robust experiments with replication and appropriate controls. A consequence of this is that we largely suffer from a lack of mechanistic understanding of the population dynamics of interacting species, which can be surprisingly complex. Mechanistic models offer an opportunity to examine the causes and consequences of some of this complexity. We present a bioenergetic mechanistic model of a tritrophic system where the primary vegetation resource follows a seasonal growth function, and the herbivore and carnivore species are modeled using two integral projection models (IPMs) with body mass as the phenotypic trait. Within each IPM, the demographic functions are structured according to bioenergetic principles, describing how animals acquire and transform resources into body mass, energy reserves, and breeding potential. We parameterize this model to reproduce the population dynamics of grass, elk, and wolves in northern Yellowstone National Park (USA) and investigate the impact of wolf reintroduction on the system. Our model generated predictions that closely matched the observed population sizes of elk and wolf in Yellowstone prior to and following wolf reintroduction. The introduction of wolves into our basal grass–elk bioenergetic model resulted in a population of 99 wolves and a reduction in elk numbers by 61% (from 14,948 to 5823) at equilibrium. In turn, vegetation biomass increased by approximately 25% in the growing season and more than threefold in the nongrowing season. The addition of wolves to the model caused the elk population to switch from being food‐limited to being predator‐limited and had a stabilizing effect on elk numbers across different years. Wolf predation also led to a shift in the phenotypic composition of the elk population via a small increase in elk average body mass. Our model represents a novel approach to the study of predator–prey interactions, and demonstrates that explicitly considering and linking bioenergetics, population demography and body mass phenotypes can provide novel insights into the mechanisms behind complex ecosystem processes.

Empirical evidence of climate change and urbanization impacts on warming stream temperatures - Vaughn Grey; Kate Smith-Miles; Tim D. Fletcher; Belinda E. Hatt; Rhys A. Coleman (Water Research, 2023)

Evaluation of cataract formation in fish exposed to environmental radiation at Chernobyl and Fukushima - Adélaïde Lerebours; Justyn Regini; Roy A. Quinlan; Toshihiro Wada; Barbara Pierscionek; Martin Devonshire; Alexia A. Kalligeraki; Alice Uwineza; Laura Young; John M. Girkin; Phil Warwick; Kurt Smith; et al. (Science of The Total Environment, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Honey bee drones are synchronously hyperactive inside the nest - Louisa C. Neubauer; Jacob D. Davidson; Benjamin Wild; David M. Dormagen; Tim Landgraf; Iain D. Couzin; Michael L. Smith (Animal Behaviour, 2023)

Evaluation of biopesticides for the control of Erwinia amylovora in apple and pear - S. Tianna DuPont; Kerik Cox; Ken Johnson; Kari Peter; Tim Smith; Misbakhul Munir; Aina Baro (Journal of Plant Pathology, 2023)
With increasing organic acreage and scrutiny of antibiotics use, alternatives to antibiotics for the control of Erwinia amylovora are of interest to stakeholders. At the same time failures of minimally tested, newly marketed products have resulted in severe infections leading to costly tree and orchard removal. We evaluated antibiotic alternatives in 8 Washington, 3 Oregon, 3 New York and 2 Pennsylvania field experiments conducted 2013 to 2022. Antibiotic alternatives included essential oils (thyme and cinnamon extracts), mineral compounds (potassium aluminum sulfate), oxidizers (peracetic acid-peroxide), soluble coppers (copper octanoate, copper hydroxide, copper sulfate pentahydrate), and biological controls ( Aureobasidium pullulans , Bacillus subtilis , bacteriophage). Studies were conducted in ‘Bartlett’ and ‘dAnjou’ pear, ‘Gala’, ‘Cameo,‘ and ‘Red Delicious’ apple with 4 to 6 single-tree replicates arranged in a randomized complete block inoculated with E. amylovora at 80–100% bloom. In summary analysis of 8 Washington trials Alum (potassium aluminum sulfate), Blossom Protect ( A. pullulans ) and several copper products (Previsto, Mastercop, Instill) provided good disease suppression of 70–73% similar to antibiotic checks. Several essential oil, copper, and peracetic acid-peroxide and biological products (Serenade Opti, Cueva, Oxidate 5.0, Jet Ag, Thyme Guard and Thymox) provided intermediate disease suppression between 45 and 62% significantly better than the water-treated control. In multistate trials Alum with 2–3 applications provided good control in most experiments (means 2019: WA 79%, NY 77%, PA 57%; 2020: OR 86%, NY 65%, WA 28%; 2021: NY 87%, WA 50%). Essential oils with 3–4 applications provided intermediate control NY 2021 81% control 23% thyme oil, 70–85% control NY 2020, 2021 60% cinnamon oil.

Simulating the source waters for the Wilkins Peak Member evaporite sequence with modern soda spring analogues - William D. Arnuk; Tim K. Lowenstein; Elizabeth M. Klonowski; Alan R. Carroll; M. Elliot Smith (Applied Geochemistry, 2023)

Peering down the sink: A review of isoprene metabolism by bacteria - Robin A. Dawson; Andrew T. Crombie; Robert S. Jansen; Thomas J. Smith; Tim Nichol; Colin Murrell (Environmental Microbiology, 2023)
Isoprene (2‐methyl‐1,3‐butadiene) is emitted to the atmosphere each year in sufficient quantities to rival methane (>500 Tg C yr −1 ), primarily due to emission by trees and other plants. Chemical reactions of isoprene with other atmospheric compounds, such as hydroxyl radicals and inorganic nitrogen species (NO x ), have implications for global warming and local air quality, respectively. For many years, it has been estimated that soil‐dwelling bacteria consume a significant amount of isoprene (~20 Tg C yr −1 ), but the mechanisms underlying the biological sink for isoprene have been poorly understood. Studies have indicated or confirmed the ability of diverse bacterial genera to degrade isoprene, whether by the canonical iso ‐type isoprene degradation pathway or through other less well‐characterized mechanisms. Here, we review current knowledge of isoprene metabolism and highlight key areas for further research. In particular, examples of isoprene‐degraders that do not utilize the isoprene monooxygenase have been identified in recent years. This has fascinating implications both for the mechanism of isoprene uptake by bacteria, and also for the ecology of isoprene‐degraders in the environments.

Molecular detection and distribution of the genera Amphidoma and Azadinium (Amphidomataceae, Dinophyceae) in the coastal waters of Aotearoa/New Zealand - Muharrem Balci; Lesley L. Rhodes; Tomohiro Nishimura; J. Sam Murray; D. Tim Harwood; A. Lincoln MacKenzie; Tony Bui; Catherine Moisan; Lucy Thompson; Kirsty F. Smith (New Zealand Journal of Marine and Freshwater Research, 2023)
Molecular‐based approaches for harmful algal bloom species, which can be difficult to identify by light microscopy, are important tools for detecting and predicting the blooms. In this study, 84 samples from Aotearoa/New Zealand coastal waters that contained Azadinium ‐like cells were analysed using an Amphidomataceae real‐time PCR assay. Nineteen samples were positive, and 24 Azadinium ‐like clonal isolates were established from these samples. Subsequently, only five isolates from one sampling point were positive using the real‐time PCR assay. Four of the five isolates were genetically identified as Amphidoma languida and one as Azadinium dalianense . The field samples were analysed retrospectively using the species‐specific real‐time PCR assays; Am. languida was detected from the temperate areas, while Az. poporum and Az. spinosum were detected at one site. Two representative strains of each species were analysed by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS), including Am. languida, which is known as toxic in the previous studies, but neither produced the currently monitored azaspiracids (AZAs). These two newly recorded species for New Zealand are important findings. The results highlight the need for more information on the spatio‐temporal variations of potentially toxic Amphidomataceae species and the risk of AZAs in New Zealand coastal waters.

Ecological consequences of historic moorland ‘improvement’ - Francis M. Rowney; Ralph M. Fyfe; Philip Anderson; Robert Barnett; William Blake; Tim Daley; Katie Head; Alison MacLeod; Ian Matthews; David N. Smith (Biodiversity and Conservation, 2022)

Regional patterns in demersal fish assemblages among subsea pipelines and natural habitats across north-west Australia - Ronen Galaiduk; Ben Radford; Mark Case; Todd Bond; Michael Taylor; Tim Cooper; Luke Smith; Dianne McLean (Frontiers in Marine Science, 2022)
Regional patterns of fish diversity, abundance, distribution, and assemblage composition are driven by a combination of biotic and abiotic conditions in the marine environment, but these conditions can be altered through anthropogenic activities, such as those associated with oil and gas extraction. The present study utilises data on fish relative abundance and diversity obtained from 1546 baited remote underwater video deployments conducted between 2004 – 2019 in depths of 9 – 170 m across 2000 km of coastline in north-west Australia on natural habitats and subsea pipelines to understand the influence of oil and gas infrastructure on fish assemblages. A total of 450 fish taxa from 56 families was observed, with populations dominated by generalist and invertebrate carnivore taxa. At the regional scale, subsea pipelines had lower diversity (lower taxonomic richness) than natural environments, but possessed a higher abundance of piscivorous and herbivorous fish taxa. Clear patterns in fish assemblage composition were observed in multivariate analyses, reflecting the proximity of oceanic shoals and banks, depth, and to a lesser extent, oil and gas infrastructure. Shallow-water and close to shoals assemblages were characterised by a diversity of site-attached (e.g., wrasses, tuskfish), reef-associated taxa (e.g., emperors). Mesophotic fish assemblages were characterised by commercially important (e.g., goldband snapper), wide-ranging (e.g., sharks) and sand-affiliated (e.g., toadfish, threadfin bream) taxa. Proximity to pipelines and platforms ranked low as predictors in the multivariate analyses suggesting a negligible regional influence of these structures on fish communities in comparison to depth and shoal habitats. Local-scale influences of subsea infrastructure, however, may be important for some fish species (infrastructure vs. immediate surrounds). Our study highlights the influence of abiotic factors on regional-scale patterns in fish assemblage structure across north-west Australia.

Long-Term Drought and Warming Alter Soil Bacterial and Fungal Communities in an Upland Heathland - Fiona M. Seaton; Sabine Reinsch; Tim Goodall; Nicola White; Davey L. Jones; Robert I. Griffiths; Simon Creer; Andy Smith; Bridget A. Emmett; David A. Robinson (Ecosystems, 2022)
The response of soil microbial communities to a changing climate will impact global biogeochemical cycles, potentially leading to positive and negative feedbacks. However, our understanding of how soil microbial communities respond to climate change and the implications of these changes for future soil function is limited. Here, we assess the response of soil bacterial and fungal communities to long-term experimental climate change in a heathland organo-mineral soil. We analysed microbial communities using Illumina sequencing of the 16S rRNA gene and ITS2 region at two depths, from plots undergoing 4 and 18 years of in situ summer drought or warming. We also assessed the colonisation of Calluna vulgaris roots by ericoid and dark septate endophytic (DSE) fungi using microscopy after 16 years of climate treatment. We found significant changes in both the bacterial and fungal communities in response to drought and warming, likely mediated by changes in soil pH and electrical conductivity. Changes in the microbial communities were more pronounced after a longer period of climate manipulation. Additionally, the subsoil communities of the long-term warmed plots became similar to the topsoil. Ericoid mycorrhizal colonisation decreased with depth while DSEs increased; however, these trends with depth were removed by warming. We largely ascribe the observed changes in microbial communities to shifts in plant cover and subsequent feedback on soil physicochemical properties, especially pH. Our results demonstrate the importance of considering changes in soil microbial responses to climate change across different soil depths and after extended periods of time.

Alternations in the foraging behaviour of a primary consumer drive patch transition dynamics in a temperate rocky reef ecosystem - Joshua G. Smith; M. Tim Tinker (Ecology Letters, 2022)
Understanding the role of animal behaviour in linking individuals to ecosystems is central to advancing knowledge surrounding community structure, stability and transition dynamics. Using 22 years of long‐term subtidal monitoring, we show that an abrupt outbreak of purple sea urchins ( Strongylocentrotus purpuratus ), which occurred in 2014 in southern Monterey Bay, California, USA, was primarily driven by a behavioural shift, not by a demographic response (i.e. survival or recruitment). We then tracked the foraging behaviour of sea urchins for 3 years following the 2014 outbreak and found that behaviour is strongly associated with patch state (forest or barren) transition dynamics. Finally, in 2019, we observed a remarkable recovery of kelp forests at a deep rocky reef. We show that this recovery was associated with sea urchin movement from the deep reef to shallow water. These results demonstrate how changes in grazer behaviour can facilitate patch dynamics and dramatically restructure communities and ecosystems.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Persistent thermally driven shift in the functional trait structure of herbivorous fishes: Evidence of top‐down control on the rebound potential of temperate seaweed forests? - Nestor E. Bosch; Matthew McLean; Salvador Zarco‐Perello; Scott Bennett; Rick D. Stuart‐Smith; Adriana Vergés; Albert Pessarrodona; Fernando Tuya; Tim Langlois; Claude Spencer; Sahira Bell; Benjamin J. Saunders; et al. (Global Change Biology, 2022)
Extreme climatic events can reshape the functional structure of ecological communities, potentially altering ecological interactions and ecosystem functioning. While these shifts have been widely documented, evidence of their persistence and potential flow‐on effects on ecosystem structure following relaxation of extreme events remains limited. Here, we investigate changes in the functional trait structure – encompassing dimensions of resource use, thermal affinity, and body size – of herbivorous fishes in a temperate reef system that experienced an extreme marine heatwave (MHW) and subsequent return to cool conditions. We quantify how changes in the trait structure modified the nature and intensity of herbivory‐related functions (macroalgae, turf, and sediment removal), and explored the potential flow‐on effects on the recovery dynamics of macroalgal foundation species. The trait structure of the herbivorous fish assemblage shifted as a result of the MHW, from dominance of cool‐water browsing species to increased evenness in the distribution of abundance among temperate and tropical guilds supporting novel herbivory roles (i.e. scraping, cropping, and sediment sucking). Despite the abundance of tropical herbivorous fishes and intensity of herbivory‐related functions declined following a period of cooling after the MHW, the underlying trait structure displayed limited recovery. Concomitantly, algal assemblages displayed a lack of recovery of the formerly dominant foundational species, the kelp Ecklonia radiata , transitioning to an alternative state dominated by turf and Sargassum spp. Our study demonstrates a legacy effect of an extreme MHW and exemplified the value of monitoring phenotypic (trait mediated) changes in the nature of core ecosystem processes to predict and adapt to the future configurations of changing reef ecosystems.

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Historical Trends of Sperm Whale (Physeter macrocephalus) Distribution in the Phoenix Archipelago - Brian R. C. Kennedy; Lara Hakam; Jan Witting; Regen Milani; Sue Taei; Tim Smith; Erin Taylor; Tooreka Teemari; Randi D. Rotjan (Frontiers in Marine Science, 2021)
The Phoenix Archipelago in the Central Pacific is situated in what was once one of the most productive areas for capturing sperm whales ( Physeter macrocephalus ). These whales were the focal targets of American offshore whalers in the mid-19th century along the equator, an area known as the “on-the-line” whaling grounds. Now, as large-scale Marine Protected Areas (MPAs) have provided protection for marine mammals and their food sources, it is important to have a solid understanding of historical baselines so recovery distributions can be compared with pre-whaling distributions. The Phoenix Islands archipelago contains two large MPAs: the Phoenix Islands Protected Area (PIPA), established by Kiribati in 2008, and the Howland/Baker unit of the Pacific Remote Islands Marine National Monument (PRIMNM), established by the United States in 2009. Using historic whaling records from American whaling vessels operated through the wider Phoenix Archipelago region, we reconstructed information about the presence and distribution of P. microcephalus throughout the 1800s within and around PIPA and the Howland/Baker units of the PRIMNM. Historical data analyzed using ArcGIS showed that sperm whales were present year-round within the study area, which is consistent with 20th century records from the Ocean Biogeographic Information System (OBIS). A Getis Ord Gi ∗ hotspot analysis also revealed sighting hotspots within PIPA and near Howland and Baker, suggesting that these two areas may be of long-term ecological importance to sperm whales in the central Pacific. The New England whaling fleet ceased whaling effort in the central Pacific in the late 1800s, and publicly available records since that time are scarce. There has been no modern systematic whale survey ever conducted within the Phoenix Archipelago, though anecdotal accounts and sightings have been compiled over the years. These intermittent accounts suggest that though whale populations have not recovered to pre-whaling baselines, large-scale MPAs may play a role in helping to foster a resurgence of marine mammal populations. As the network of large-scale MPAs continue to grow as part of the commitment to ocean conservation set forth by UNESCO, IUCN, and the UN Decade for Ocean Science, historical baselines will be critical as a “yardstick” to measure population resurgence success for each MPA, and for populations overall.

Treatment cost and access to care: experiences of young women diagnosed with breast cancer - Sujha Subramanian; Florence K. L. Tangka; Patrick Edwards; Madeleine Jones; Tim Flanigan; Jenya Kaganova; Kevin Smith; Cheryll C. Thomas; Nikki A. Hawkins; Juan L. Rodriguez; Gery P. Guy; Temeika Fairley (Cancer Causes & Control, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

What We Have Learned From the Framework for Ocean Observing: Evolution of the Global Ocean Observing System - Toste Tanhua; Andrea McCurdy; Albert Fischer; Ward Appeltans; Nicholas Bax; Kim Currie; Brad DeYoung; Daniel Dunn; Emma Heslop; Linda K. Glover; John Gunn; Katherine Hill; et al. (Frontiers in Marine Science, 2019)

The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Ship-Based Contributions to Global Ocean, Weather, and Climate Observing Systems - Shawn R. Smith; Gaël Alory; Axel Andersson; William Asher; Alex Baker; David I. Berry; Kyla Drushka; Darin Figurskey; Eric Freeman; Paul Holthus; Tim Jickells; Henry Kleta; et al. (Frontiers in Marine Science, 2019)

The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

Environmental influences on stem borer incidence in Australian subtropical Corymbia plantations - Valerie J. Debuse; Tim E. Smith; Chris T. Holloway; Aaron N. Wiegand; Helen F. Nahrung; Simon A. Lawson (Journal of Pest Science, 2019)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The dinoflagellate genera Gambierdiscus and Ostreopsis from subtropical Raoul Island and North Meyer Island, Kermadec Islands - Lesley L. Rhodes; Kirsty F. Smith; Arjun Verma; Sam Murray; D. Tim Harwood; Tom Trnski (New Zealand Journal of Marine and Freshwater Research, 2017)
An expedition to North Meyer Island, Kermadec Islands, in November 2015, resulted in the isolation of two Gambierdiscus species, G. australes and a previously unknown Gambierdiscus species maintained in the Cawthron Institute Culture Collection of Micro‐algae as CAWD242. Identifications were based on morphology and DNA sequence data analysis. Nine isolates of G. australes produced maitotoxin‐1 (MTX‐1) ranging from present (detectable but below the confidence level) to 36.6 pg per cell. One further isolate did not produce MTX‐1, but all G. australes isolates produced putative MTX‐3. Isolate CAWD242 was negative for MTX‐1 but produced MTX‐3. Ostreopsis sp. 3 isolated from samples collected during an earlier expedition in 2013 produced low concentrations of palytoxin (PLTX)‐like compounds (0.013 pg per cell), but an isolate of the same species from samples collected in 2015 was non‐toxic. Other dinoflagellates isolated and identified were Coolia malayensis , Amphidinium carterae and Prorocentrum hoffmannianum .

Car8 dorsal root ganglion expression and genetic regulation of analgesic responses are associated with a cis-eQTL in mice - Roy C. Levitt; Gerald Y. Zhuang; Yuan Kang; Diana M. Erasso; Udita Upadhyay; Mehtap Ozdemir; Eugene S. Fu; Konstantinos D. Sarantopoulos; Shad B. Smith; William Maixner; Luda Diatchenko; Eden R. Martin; et al. (Mammalian Genome, 2017)

Growth and physiological responses of teak (Tectona grandis Linn. f.) clones to Ca, H and Al stresses in solution and acid soils - J. Bernhard Wehr; F. Pax C. Blamey; Tim E. Smith; Neal W. Menzies (New Forests, 2017)

A sperm whale's perspective: The importance of seasonality and seamount depth - Courtney H. Hann; Tim D. Smith; Leigh G. Torres (Marine Mammal Science, 2016)

A spatially explicit estimate of the prewhaling abundance of the endangered North Atlantic right whale - Sophie Monsarrat; M. Grazia Pennino; Tim D. Smith; Randall R. Reeves; Christine N. Meynard; David M. Kaplan; Ana S.L. Rodrigues (Conservation Biology, 2016)
The North Atlantic right whale (NARW) (Eubalaena glacialis) is one of the world's most threatened whales. It came close to extinction after nearly a millennium of exploitation and currently persists as a population of only approximately 500 individuals. Setting appropriate conservation targets for this species requires an understanding of its historical population size, as a baseline for measuring levels of depletion and progress toward recovery. This is made difficult by the scarcity of records over this species’ long whaling history. We sought to estimate the preexploitation population size of the North Atlantic right whale and understand how this species was distributed across its range. We used a spatially explicit data set on historical catches of North Pacific right whales (NPRWs) (Eubalaena japonica) to model the relationship between right whale relative density and the environment during the summer feeding season. Assuming the 2 right whale species select similar environments, we projected this model to the North Atlantic to predict how the relative abundance of NARWs varied across their range. We calibrated these relative abundances with estimates of the NPRW total prewhaling population size to obtain high and low estimates for the overall NARW population size prior to exploitation. The model predicted 9,075–21,328 right whales in the North Atlantic. The current NARW population is thus

Response to “Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al” - Alexandra C. G. Thomson; Paul H. York; Tim M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2016)

Detection of Azadinium poporum in New Zealand: the use of molecular tools to assist with species isolations - Kirsty F. Smith; Lesley Rhodes; D. Tim Harwood; Janet Adamson; Catherine Moisan; Rex Munday; Urban Tillmann (Journal of Applied Phycology, 2016)

Concentration and retention of T oxoplasma gondii oocysts by marine snails demonstrate a novel mechanism for transmission of terrestrial zoonotic pathogens in coastal ecosystems - Colin Krusor; Woutrina A. Smith; M. Tim Tinker; Mary Silver; Patricia A. Conrad; Karen Shapiro (Environmental Microbiology, 2015)
Summary The parasite T oxoplasma gondii is an environmentally persistent pathogen that can cause fatal disease in humans, terrestrial warm‐blooded animals and aquatic mammals. Although an association between T . gondii exposure and prey specialization on marine snails was identified in threatened C alifornia sea otters, the ability of kelp‐dwelling snails to transmit terrestrially derived pathogens has not been previously investigated. The objective of this study was to measure concentration and retention of T . gondii by marine snails in laboratory aquaria, and to test for natural T . gondii contamination in field‐collected snails. Following exposure to T . gondii ‐containing seawater, oocysts were detected by microscopy in snail faeces and tissues for 10 and 3 days respectively. Nested polymerase chain reaction was also applied as a method for confirming putative T . gondii oocysts detected in snail faeces and tissues by microscopy. T oxoplasma gondii was not detected in field‐collected snails. Results suggest that turban snails are competent transport hosts for T . gondii . By concentrating oocysts in faecal pellets, snails may facilitate entry of T . gondii into the nearshore marine food web. This novel mechanism also represents a general pathway by which marine transmission of terrestrially derived microorganisms can be mediated via pathogen concentration and retention by benthic invertebrates.

Diverse phenotypic consequences of mutations affecting the C-terminus of FLNA - Margriet van Kogelenberg; Alice R. Clark; Zandra Jenkins; Tim Morgan; Ananda Anandan; Gregory M. Sawyer; Matthew Edwards; Tracy Dudding; Tessa Homfray; Bruce Castle; John Tolmie; Fiona Stewart; et al. (Journal of Molecular Medicine, 2015)

The cost of reproduction: differential resource specialization in female and male California sea otters - Emma A. Elliott Smith; Seth D. Newsome; James A. Estes; M. Tim Tinker (Oecologia, 2015)

The US Navy Coupled Ocean-Wave Prediction System - Richard Allard; Erick Rogers; Paul Martin; Tommy Jensen; Philip Chu; Tim Campbell; James Dykes; Travis Smith; Jeikook Choi; Uriah Gravois (Oceanography, 2014)

Measurement of Subvisible Particulates in Lyophilised Erwinia chrysanthemi l-asparaginase and Relationship with Clinical Experience - David Gervais; Tim Corn; Andrew Downer; Stuart Smith; Alan Jennings (The AAPS Journal, 2014)

A synthesis of methane emissions from 71 northern, temperate, and subtropical wetlands - Merritt R. Turetsky; Agnieszka Kotowska; Jill Bubier; Nancy B. Dise; Patrick Crill; Ed R. C. Hornibrook; Kari Minkkinen; Tim R. Moore; Isla H. Myers‐Smith; Hannu Nykänen; David Olefeldt; Janne Rinne; et al. (Global Change Biology, 2014)
Wetlands are the largest natural source of atmospheric methane. Here, we assess controls on methane flux using a database of approximately 19 000 instantaneous measurements from 71 wetland sites located across subtropical, temperate, and northern high latitude regions. Our analyses confirm general controls on wetland methane emissions from soil temperature, water table, and vegetation, but also show that these relationships are modified depending on wetland type (bog, fen, or swamp), region (subarctic to temperate), and disturbance. Fen methane flux was more sensitive to vegetation and less sensitive to temperature than bog or swamp fluxes. The optimal water table for methane flux was consistently below the peat surface in bogs, close to the peat surface in poor fens, and above the peat surface in rich fens. However, the largest flux in bogs occurred when dry 30‐day averaged antecedent conditions were followed by wet conditions, while in fens and swamps, the largest flux occurred when both 30‐day averaged antecedent and current conditions were wet. Drained wetlands exhibited distinct characteristics, e.g. the absence of large flux following wet and warm conditions, suggesting that the same functional relationships between methane flux and environmental conditions cannot be used across pristine and disturbed wetlands. Together, our results suggest that water table and temperature are dominant controls on methane flux in pristine bogs and swamps, while other processes, such as vascular transport in pristine fens, have the potential to partially override the effect of these controls in other wetland types. Because wetland types vary in methane emissions and have distinct controls, these ecosystems need to be considered separately to yield reliable estimates of global wetland methane release.

Breeding for value in a changing world: past achievements and future prospects - Tim White; John Davis; Salvador Gezan; Jiri Hulcr; Eric Jokela; Matias Kirst; Timothy A. Martin; Gary Peter; Greg Powell; Jason Smith (New Forests, 2014)

Integrated assessment models for ecologists: the present and the future - Michael Harfoot; Derek P. Tittensor; Tim Newbold; Greg McInerny; Matthew J. Smith; Jörn P. W. Scharlemann (Global Ecology and Biogeography, 2014)
Aim Human impacts on the biosphere are a matter of urgent and growing concern, with ecologists increasingly being asked to project biodiversity futures. The Intergovernmental Platform on Biodiversity and Ecosystem Services ( IPBES ) is likely to comprehensively assess such projections, yet despite being widely used and potentially critical tools for analysing socio‐environmental futures, integrated assessment models ( IAM s) have received little attention from ecological modellers. We aim to raise awareness and understanding of IAM s among ecologists by describing the structure and composition of IAM s, assessing their utility for biodiversity projections and identifying limitations that hamper greater interaction between scientists using IAMs and those using ecological models. We also hope to inspire more accessible and applicable models by suggesting development needs for IAM s. Methods We conduct a systematic review of four state‐of‐the‐art IAM s, which describes and contrasts key model features and analyses six aspects of IAM s that are of fundamental interest to ecologists. Conclusions IAM s could be valuable for modelling biodiversity futures; however, current IAM s were not developed for this application and challenges remain for ecologists looking to use their outputs. Separating and understanding the differences resulting from IAM formulation and those resulting from specific scenario assumptions is currently problematic, and current IAM s may be unable to accurately represent environmental conditions for both Earth‐system projections and for building robust models of biodiversity because key ecological processes are absent. We suggest that model intercomparisons would identify differences in model dynamics, and detailed studies of how dynamical interactions between components influence behaviour would address why such differences arise. Bio‐economic fisheries models and agriculture pollination models provide starting points for integrating key ecological feedbacks within IAM s. Ultimately, making IAM s more accessible within the multidisciplinary study of global change, drawing on user‐centred research, would enable more resolved, reliable and accurate assessment of how Earth's socio‐ecological system is approaching planetary boundaries.

Integrating multiple lines of evidence to better understand the evolutionary divergence of humpback dolphins along their entire distribution range: a new dolphin species in Australian waters? - Martin Mendez; Thomas A. Jefferson; Sergios‐Orestis Kolokotronis; Michael Krützen; Guido J. Parra; Tim Collins; Giana Minton; Robert Baldwin; Per Berggren; Anna Särnblad; Omar A. Amir; Vic M. Peddemors; et al. (Molecular Ecology, 2013)
The conservation of humpback dolphins, distributed in coastal waters of the Indo‐West Pacific and eastern Atlantic Oceans, has been hindered by a lack of understanding about the number of species in the genus ( Sousa ) and their population structure. To address this issue, we present a combined analysis of genetic and morphologic data collected from beach‐cast, remote‐biopsied and museum specimens from throughout the known Sousa range. We extracted genetic sequence data from 235 samples from extant populations and explored the mitochondrial control region and four nuclear introns through phylogenetic, population‐level and population aggregation frameworks. In addition, 180 cranial specimens from the same geographical regions allowed comparisons of 24 morphological characters through multivariate analyses. The genetic and morphological data showed significant and concordant patterns of geographical segregation, which are typical for the kind of demographic isolation displayed by species units, across the Sousa genus distribution range. Based on our combined genetic and morphological analyses, there is convincing evidence for at least four species within the genus ( S. teuszii in the Atlantic off West Africa, S. plumbea in the central and western Indian Ocean, S. chinensis in the eastern Indian and West Pacific Oceans, and a new as‐yet‐unnamed species off northern Australia).

Myocardial perfusion distribution and coronary arterial pressure and flow signals: clinical relevance in relation to multiscale modeling, a review - Froukje Nolte; Eoin R. Hyde; Cristina Rolandi; Jack Lee; Pepijn van Horssen; Kal Asrress; Jeroen P. H. M. van den Wijngaard; Andrew N. Cookson; Tim van de Hoef; Radomir Chabiniok; Reza Razavi; Christian Michler; et al. (Medical & Biological Engineering & Computing, 2013)

Heritability of adventitious rooting of grapevine dormant canes - Brady P. Smith; Matthew S. Wheal; Tim H. Jones; Norma B. Morales; Peter R. Clingeleffer (Tree Genetics & Genomes, 2013)

Acute anxiety increases the magnitude of the cold shock response before and after habituation - Martin James Barwood; Jo Corbett; Richard Green; Tim Smith; Perry Tomlin; Lydia Weir-Blankenstein; Michael J. Tipton (European Journal of Applied Physiology, 2013)

Simulation of carbon pool changes in woodlots in eastern Zambia using the CO2FIX model - Martin L. Kaonga; Tim P. Bayliss-Smith (Agroforestry Systems, 2012)

Workshop on the ecosystem and fisheries of the Coral Sea: an Australian perspective on research and management - Jock W. Young; A. David McKinnon; Daniela Ceccarelli; Richard Brinkman; Rodrigo H. Bustamante; Mike Cappo; Cathy Dichmont; Peter Doherty; Miles Furnas; Daniel Gledhill; Shane Griffiths; Trevor Hutton; et al. (Reviews in Fish Biology and Fisheries, 2012)

Temperature oscillations may shorten male lifespan via natural selection in utero - Ralph A. Catalano; Tim A. Bruckner; Kirk R. Smith; Katherine B. Saxton (Climatic Change, 2012)

The potential role of microRNAs in regulating gonadal sex differentiation in the chicken embryo - Andrew D. Cutting; Stephanie C. Bannister; Tim J. Doran; Andrew H. Sinclair; Mark V. L. Tizard; Craig A. Smith (Chromosome Research, 2012)

A rapid detection method for apoptosis and necrosis measurement using the Cellometer imaging cytometry - Leo Li-Ying Chan; Ning Lai; Elena Wang; Tim Smith; Xifeng Yang; Bo Lin (Apoptosis, 2011)

Effects of nutrient addition on leaf chemistry, morphology, and photosynthetic capacity of three bog shrubs - Jill L. Bubier; Rose Smith; Sari Juutinen; Tim R. Moore; Rakesh Minocha; Stephanie Long; Subhash Minocha (Oecologia, 2011)

The integration of land and marine spatial planning - Hance D. Smith; Frank Maes; Tim A. Stojanovic; Rhoda C. Ballinger (Journal of Coastal Conservation, 2011)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Diet of black guillemots and northern fulmars breeding beside a High Arctic polynya - Tim Byers; Alan Smith; Mark L. Mallory (Polar Biology, 2010)

Allometric models for estimation of aboveground carbon stocks in improved fallows in eastern Zambia - Martin L. Kaonga; Tim P. Bayliss-Smith (Agroforestry Systems, 2010)

Carbon pools in tree biomass and the soil in improved fallows in eastern Zambia - Martin L. Kaonga; Tim P. Bayliss-Smith (Agroforestry Systems, 2009)

Principles and application of an in vivo swine assay for the determination of arsenic bioavailability in contaminated matrices - Matthew Rees; Lloyd Sansom; Allan Rofe; Albert L. Juhasz; Euan Smith; John Weber; Ravi Naidu; Tim Kuchel (Environmental Geochemistry and Health, 2009)

Complex modulation of L-type Ca2+ current inactivation by sorcin in isolated rabbit cardiomyocytes - Mark R. Fowler; Gianni Colotti; Emilia Chiancone; Yoshiharu Higuchi; Tim Seidler; Godfrey L. Smith (Pflügers Archiv - European Journal of Physiology, 2009)

Geostatistical analysis of biomarkers of genotoxicity in cattle, Bos taurus and Bos taurus × Bos indicus, sentinels near industrial facilities - Wesley Bissett; Roger Smith; L. Garry Adams; Robert Field; William Moyer; Tim Phillips; H. Morgan Scott; James A. Thompson (Ecotoxicology, 2009)

Historical distribution of right whales in the North Pacific - Elizabeth Josephson; Tim D Smith; Randall R Reeves (Fish and Fisheries, 2008)
Fisheries records provide some of the only information on pre‐fishing distribution and abundance for species that were depleted before the advent of modern scientific investigations. This paper interprets records of the early history of whaling for North Pacific right whales ( Eubalaena pacifica ). The current population occupies only a fraction of its historical range. Historical distributions of several whale species have been inferred from charts prepared by Matthew Fontaine Maury in the early 1850s and Charles Haskins Townsend in the 1930s based on data from American whalers’ logbooks. In the North Pacific, Maury’s chart has been interpreted to show that right whales occurred continuously across the entire basin. However, we find plotting errors when we compare the North Pacific chart to the corresponding data worksheets prepared for Maury (the ‘Maury Abstracts’) and the chart appears to have misled historians and biologists. Although these charts and those in the North Atlantic are wrong, the Maury Abstracts themselves appear largely consistent with the original whaler logbooks. Our analysis shows that right whales were likely not distributed continuously across the North Pacific, but instead had a pronounced longitudinally bimodal distribution and were encountered infrequently in the central‐northern North Pacific. This work shows how valuable information can be obtained by examining original source material. The American whaling logbooks are extensive and have been largely overlooked in studies of whale populations.

Balancing bias and precision in capture‐recapture estimates of abundance - Nancy A. Friday; Tim D. Smith; Peter T. Stevick; Judy Allen; Tom Fernald (Marine Mammal Science, 2008)
Capture‐recapture estimates of abundance using photographic identification data are sensitive to the quality of photographs used and distinctiveness of individuals in the population. Here analyses are presented for examining the effects of photographic quality and individual animal distinctiveness scores and for objectively selecting a subset of data to use for capture‐recapture analyses using humpback whale ( Megaptera novaeangliae ) data from a 2‐year study in the North Atlantic. Photographs were evaluated for their level of quality and whales for their level of individual distinctiveness. Photographic quality scores had a 0.21 probability of changing by a single‐quality level, and there were no changes by two or more levels. Individual distinctiveness scores were not independent of photographic quality scores. Estimates of abundance decreased as poor‐quality photographs were removed. An appropriate balance between precision and bias in abundance estimates was achieved by removing the lowest‐quality photographs and those of incompletely photographed flukes given our assumptions about the true population abundance. A simulation of the selection process implied that, if the estimates are negatively biased by heterogeneity, the increase in bias produced by decreasing the sample size is not more than 2%. Capture frequencies were independent of individual distinctiveness scores.

Wetlands as landscape units: spatial patterns in salinity and water chemistry - Michael J. Smith; E. Sabine G. Schreiber; Michele Kohout; Keely Ough; Ruth Lennie; Derek Turnbull; Changhao Jin; Tim Clancy (Wetlands Ecology and Management, 2007)

USING HISTORICAL RECORDS TO RELOCATE A LONG‐FORGOTTEN SUMMER FEEDING GROUND OF NORTH ATLANTIC RIGHT WHALES - Tim D. Smith; Klaus Barthelmess; Randall R. Reeves (Marine Mammal Science, 2006)

Locus heterogeneity in autosomal recessive congenital cataracts: linkage to 9q and germline HSF4 mutations - Tim Forshew; Colin A. Johnson; Shagufta Khaliq; Shanaz Pasha; Catherine Willis; Rashida Abbasi; Louise Tee; Ursula Smith; Richard C. Trembath; Syed Qasim Mehdi; Anthony T. Moore; Eamonn R. Maher (Human Genetics, 2005)

Phylogenetic relationships of spatangoid sea urchins (Echinoidea): taxon sampling density and congruence between morphological and molecular estimates - Bruce Stockley; Andrew B. Smith; Tim Littlewood; Harilaos A. Lessios; Jacqueline A. Mackenzie‐Dodds (Zoologica Scripta, 2005)
A phylogeny for 21 species of spatangoid sea urchins is constructed using data from three genes and results compared with morphology‐based phylogenies derived for the same taxa and for a much larger sample of 88 Recent and fossil taxa. Different data sets and methods of analysis generate different phylogenetic hypotheses, although congruence tests show that all molecular approaches produce trees that are congruent with each other. By contrast, the trees generated from morphological data differ significantly according to taxon sampling density and only those with dense sampling (after a posteriori weighting) are congruent with molecular estimates. With limited taxon sampling, secondary reversals in deep‐water taxa are interpreted as plesiomorphies, pulling them to a basal position. The addition of fossil taxa with their unique character combinations reveals hidden homoplasy and generates a phylogeny that is compatible with molecular estimates. As homoplasy levels were found to be broadly similar across different anatomical structures in the echinoid test, no one suite of morphological characters can be considered to provide more reliable phylogenetic information. Some traditional groupings are supported, including the grouping of Loveniidae, Brissidae and Spatangidae within the Micrasterina, but the Asterostomatidae is shown to be polyphyletic with members scattered amongst at least five different clades. As these are mostly deep‐sea taxa, this finding implies multiple independent invasions into the deep sea.

Signature of recent historical events in the European Y-chromosomal STR haplotype distribution - Lutz Roewer; Peter J. P. Croucher; Sascha Willuweit; Tim T. Lu; Manfred Kayser; Rdiger Lessig; Peter de Knijff; Mark A. Jobling; Chris Tyler-Smith; Michael Krawczak (Human Genetics, 2005)

Autopsy your dead…and living: a proposal for fisheries science, fisheries management and fisheries - Tim D. Smith; Jason S. Link (Fish and Fisheries, 2005)
Ghoti papers Ghoti aims to serve as a forum for stimulating and pertinent ideas. Ghoti publishes succinct commentary and opinion that addresses important areas in fish and fisheries science. Ghoti contributions will be innovative and have a perspective that may lead to fresh and productive insight of concepts, issues and research agendas. All Ghoti contributions will be selected by the editors and peer reviewed. Etymology of Ghoti George Bernard Shaw (1856‐1950), polymath, playwright, Nobel prize winner, and the most prolific letter writer in history, was an advocate of English spelling reform. He was reportedly fond of pointing out its absurdities by proving that ‘fish’ could be spelt ‘ghoti’. That is: ‘gh’ as in ‘rough’, ‘o’ as in ‘women’ and ‘ti’ as in palatial. Abstract Concerns abound about the state of the world's fisheries, and by association fisheries science and fisheries management. An important question is the cause of the problems with fisheries, which are managed based on advice given by practioners of the discipline of fisheries science. These scientists provide advice in two distinct forms, one ‘policy supporting’ and the other ‘policy forming’. Policy supporting advice is given within an existing management setting and is typically provided only after rigorous and standardized evaluation. In contrast, there is no formal basis for evaluating policy‐forming advice. Criteria for evaluating the adequacy of policy forming advice are difficult to define, and the absence of such criteria poses difficulties for both fisheries scientists and managers. Following a medical practice analogy, we propose rigorously conducting ‘autopsies’ of fisheries as an approach for evaluating policy‐forming advice. A systematic approach to conducting such autopsies is suggested, with the recognition that this may be crucial for the further development of fisheries science as a scientific discipline rather than as an art form.

HISTORICAL OBSERVATIONS OF HUMPBACK AND BLUE WHALES IN THE NORTH ATLANTIC OCEAN: CLUES TO MIGRATORY ROUTES AND POSSIBLY ADDITIONAL FEEDING GROUNDS - Randall R. Reeves; Tim D. Smith; Elizabeth A. Josephson; Phillip J. Clapham; Gillian Woolmer (Marine Mammal Science, 2004)
A bstract The seasonal distributions of humpback and blue whales ( Megaptera novaeangliae and Balaenoptera musculus , respectively) in the North Atlantic Ocean are not fully understood. Although humpbacks have been studied intensively in nearshore or coastal feeding and breeding areas, their migratory movements between these areas have been largely inferred. Blue whales have only been studied intensively along the north shore of the Gulf of St. Lawrence, and their seasonal occurrence and movements elsewhere in the North Atlantic are poorly known. We investigated the historical seasonal distributions of these two species using sighting and catch data extracted from American 18th and 19th century whaling logbooks. These data suggest that humpback whales migrated seasonally from low‐latitude calving/ breeding grounds over a protracted period, and that some of them traveled far offshore rather than following coastal routes. Also, at least some humpbacks apparently fed early in the summer west of the Mid‐Atlantic Ridge, well south of their known present‐day feeding grounds. In assessing the present status of the North Atlantic humpback population, it will be important to determine whether such offshore feeding does in fact occur. Blue whales were present across the southern half of the North Atlantic during the autumn and winter months, and farther north in spring and summer, but we had too few data points to support inferences about these whales' migratory timing and routes.

Investigations in commonness and rarity: a comparative analysis of co‐occurring, congeneric Mexican trees - Colleen K. Kelly; Helena Banyard Smith; Yvonne M. Buckley; Rebecca Carter; Miguel Franco; William Johnson; Tim Jones; Ben May; Rubèn Pèrez Ishiwara; Alfredo Pèrez‐Jimènez; Arturo Solis Magallanes; Helen Steers; et al. (Ecology Letters, 2001)
Population size distributions were examined for 12 species of trees co‐occurring at Chamela Biological Station in Jalisco, Mexico. Species had been selected as congeneric pairs and trios similar in gross morphology and ecology in order better to identify correlates of relative abundance. Rarer species were found unanimously to have more irregular distributions of individuals among size classes than more common species when distributions were compared to a smooth, descending curve constructed from population mean stem diameters (an exponential distribution). Examination among species of patterns of deviation from these corresponding smooth distributions indicates that the most reasonably inferred cause for the observed pattern is consistent differences in degree of fluctuation in recruitment into adult size classes. These results thereby suggest a demographic difference between locally rarer and more common species that may be generally associated with observed differences in relative abundance and indicate a focus for management of rarity in forest trees.

Association of ErbB2 Ser1113 phosphorylation with epidermal growth factor receptor co-expression and poor prognosis in human breast cancer - Xiaomei Ouyang; Tim Gulliford; Hongyi Zhang; Gillian Smith; Guocai Huang; Richard J. Epstein (Molecular and Cellular Biochemistry, 2001)

MEASUREMENT OF PHOTOGRAPHIC QUALITY AND INDIVIDUAL DISTINCTIVENESS FOR THE PHOTOGRAPHIC IDENTIFICATION OF HUMPBACK WHALES, MEGAPTERA NOVAEANGLIAE - Nancy Friday; Tim D. Smith; Peter T. Stevick; Judy Allen (Marine Mammal Science, 2000)
A bstract Accurate identification of humpback whales from photographic identification data depends on the quality of the photographs and the distinctiveness of the flukes. Criteria for evaluating photographic quality and individual distinctiveness were developed involving judgments about overall quality or distinctiveness and about specific aspects of each. These criteria were tested for the level of agreement among judges. The distinctiveness scheme was tested for the independence of distinctiveness judgments and photographic quality. Our results show that judges could agree when evaluating specific and overall aspects of photographic quality and individual distinctiveness. The level of agreement varied for different pairs of judges, and less adept judges were identified. Ability to agree on evaluations of photographic quality was independent of the experience of the judges. Overall photographic quality and overall distinctiveness were successfully predicted from more specific variables, but the agreement between judges for these was not significantly greater than the agreement for the overall measures judged directly. There was no correlation between individual distinctiveness and photographic quality for four of the five judges, but the power of this rest may be low. Analyses of photographic identification data frequently require evaluations of photographic quality and individual distinctiveness. To obtain reliable results from such analyses, evaluation schemes and judges should be tested to ensure reliable and consistent evaluations.

H-OBIS: A Historical Dimension to the Ocean Biogeographical Information System - David Starkey; Poul Holm; Tim Smith; Robert Francis; Helen Rozwadowski (Oceanography, 2000)

“Simultaneous and Complementary Advances”: Mid-century Expectations of the Interaction of Fisheries Science and Management - Tim D. Smith (Reviews in Fish Biology and Fisheries, 1998)

A HAND‐HELD, PEN‐BASED COMPUTER SYSTEM FOIR MARINE MAMMAL SIGHTING SURVEYS - Nan Garrett Logan; Tim Smith (Marine Mammal Science, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)